Exploring Potentialities in a Child - Banerjee, Aditi (JOURNAL OF INDIAN EDUCATION, 2015)
The goal of this paper is locating schools and prevalent pedagogic practices in the context of the debate on Democracy and Citizenship. The paper tries to explore the current scenario of the schools which lacks dialogue in classrooms which in turn makes the students uniform followers of an institution which provides no space for imagination and creativity. It explores the classroom setting taking into consideration variables like the teacher, learning environment, textbooks and the student himself. This article talks about the evaluation system and examination as a tool to create hierarchy and to perpetuate fear in the students making learning a burden. Finally it talks about education as a journey of endless possibilities.